Comparing computational fluid dynamics and inverse dynamics methodologies to assess passive drag during swimming gliding - Costa, L. C.; Ribeiro, J.; Marinho, D.; Mantha, V.; Vilas-Boas, J. P.; Fernandes, R. J.; Silva, A.; Rouboa, A.; Machado, L. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of the present study was to compare two different methodologies for passive drag evaluation considering two different swimming glide positions used in the breaststroke event: a prone position with flexed shoulders and arms extended above the head, and a prone position with arms extended along the trunk. Experimentally the passive drag was assessed by Inverse Dynamics from swim meter data, and numerical simulation by the Computational Fluid Dynamics. Similar drag and drag coefficient values were found for the first glide position with the two methods; however, for the second glide position, the drag and drag coefficients were higher using Computational Fluid Dynamic when compared with Inverse Dynamics for the same velocities.